Effects of Pentoxifylline on Equine Epididymal Sperm - Guasti, Priscilla N.; Monteiro, Gabriel A.; Maziero, Rosiara R.; Martin, Ian; Avanzi, Bruno R.; Dell'aqua Junior, José Antônio [UNESP]; Papa, Frederico Ozanam [UNESP] (Elsevier, 2013)
This study evaluated whether pentoxifylline (PTX) present in the flushing extender influenced the function of equine epididymal spermatozoa after recovery and after thawing. For this experiment, 58 testicles from 29 Brazilian Jumping Horses were used. Cauda epididymides of each stallion were separated and flushed with a skim milk extender, with or without 7.18 mM PTX and then subjected to the freezing process. Samples flushed with the extender containing PTX showed a significant increase in total motility, progressive motility, straight line velocity, curvilinear velocity, and percentage of rapid sperm immediately after the recovery of epididymal sperm and after 15 minutes of incubation at 37°C (P < .05). However, the presence of PTX in the flushing extender did not affect the post-thaw motility parameters or plasma membrane integrity (P > .05). The results of this study showed that the PTX present in the flushing extender improved motility parameters of recently recovered epididymal sperm and had no deleterious effects on plasma membrane integrity and freezability of equine epididymal sperm. © 2013 Elsevier Inc. All rights reserved.
Keywords: Cryopreservation; Epididymal Spermatozoa; Pentoxifylline; Sperm Viability; Stallion